Hubungan Antara Dukungan Keluarga dengan Pemenuhan Kebutuhan Spiritual pada Lansia di Desa Surodadi Kecamatan Sayung - Sindi Ira Winanta; Iskim Luthfa (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2026)
Older adulthood was the final stage of life characterized by physical, psychological, social, and spiritual changes. At this stage, fulfilling spiritual needs becomes very important as it provides a sense of peace, meaning in life, and readiness to face the aging process. Family support serves as a major contributing factor in helping older adults maintain and enhance the fulfillment of their spiritual needs. Methods: This study employed a descriptive correlational design with a cross-sectional approach. The sample consisted of 157 older adults selected through non-probability sampling techniques. Data were collected using a family support questionnaire and the Daily Spiritual Experience Scale (DSES). Data were analyzed using Somers’ d with a significance level of 0.05. Results: The results showed that family support was in the good category (59.2%), and the fulfillment of spiritual needs was in the high category (72%). The Somers’ d test yielded a p-value of 0.000 and a correlation coefficient of 0.373. These findings indicate a significant relationship with a weak correlation strength and a positive direction. Conclusion: The better the family support provided, the higher the fulfillment of spiritual needs among older adults.